A Bacillus thuringiensis Chitin-Binding Protein is Involved in Insect Peritrophic Matrix Adhesion and Takes Part in the Infection Process - Jiaxin Qin; Zongxing Tong; Yiling Zhan; Christophe Buisson; Fuping Song; Kanglai He; Christina Nielsen-LeRoux; Shuyuan Guo (Toxins, 2020)
Bacillus thuringiensis (Bt) is used for insect pest control, and its larvicidal activity is primarily attributed to Cry toxins. Other factors participate in infection, and limited information is available regarding factors acting on the peritrophic matrix (PM). This study aimed to investigate the role of a Bt chitin-binding protein (CBPA) that had been previously shown to be expressed at pH 9 in vitro and could therefore be expressed in the alkaline gut of lepidopteron larvae. A ∆cbpA mutant was generated that was 10-fold less virulent than wild-type Bt HD73 towards Ostrinia furnacalis neonate larvae, indicating its important role in infection. Purified recombinant Escherichia coli CBPA was shown to have a chitin affinity, thus indicating a possible interaction with the chitin-rich PM. A translational GFP–CBPA fusion elucidated the localization of CBPA on the bacterial surface, and the transcriptional activity of the promoter PcbpA was immediately induced and confirmed at pH 9. Next, in order to connect surface expression and possible in vivo gut activity, last instar Galleria mellonella (Gm) larvae (not susceptible to Bt HD-73) were used as a model to follow CBPA in gut expression, bacterial transit, and PM adhesion. CBPA-GFP was quickly expressed in the Gm gut lumen, and more Bt HD73 strain bacteria adhered to the PM than those of the ∆cbpA mutant strain. Therefore, CBPA may help to retain the bacteria, via the PM binding, close to the gut surface and thus takes part in the early steps of Bt gut interactions.